IDENTIFICATION OF THE CONCEPT OF INTELLECTUAL CAPITAL AND ITS DEVELOPMENT TRENDS IN THE CONTEXT OF INNOVATIVE DEVELOPMENT OF DOMESTIC INDUSTRIAL ENTERPRISES - Nahorniak , H. S. (The actual problems of regional economy development, 2024)
The purpose of the article is to analyze existing studies on the identification of the intellectual capital of an enterprise, trends in their development, and the determination of the main components of intellectual capital in the context of the innovative development of domestic industrial enterprises. The following methods were used to conduct the research: abstract-logical method; generalization method. The results of a comparative analysis of the works of Ukrainian and foreign scientists, economists and experts on the study of the intellectual capital of an industrial enterprise are presented. Such key concepts as: intellectual capital, intangible assets, intellectual resources, human and organizational capital are systematized and unified. The meaning and role of intellectual capital is analyzed. The author's definition of the concept of "intellectual capital of the enterprise" is proposed. The main tasks of the formation of human capital under the conditions of innovative development of an industrial enterprise are outlined. The criteria for the formation of human capital as an important component of intellectual capital in the context of innovative growth of an industrial enterprise are structured. The criteria for the formation of human capital as an important component of intellectual capital in the context of innovative growth of an industrial enterprise are structured. The peculiarities of the formation of human capital under the condition of innovative development of an industrial enterprise are revealed. In the process of researching the intellectual capital of industrial enterprises, conclusions and proposals are made under the prism of the specifics of the formation of its constituent elements in the era of the formation and development of the knowledge economy. The leading vector of the further development of the intellectual capital of enterprises in the conditions of such an economy should be the issue of designing the process of cumulation, classification, measurement and transformation of knowledge capital, as well as the development of tools for transferring its elements into materialized and innovative assets of the enterprise. The practical significance of the study lies in the possibility of using the proposed provisions to ensure the effectiveness of the formation, development and use of intellectual capital in order to increase the effective functioning of industrial enterprises and the formation of competitiveness in the conditions of the activation of innovative processes.